Industrializing the University-SME Commercialization: A Conceptual Study of Commercialization Industry in Malaysia. - R., Thevendran; A. P. , Puvanasvaran (Penerbit UTeM, 2012)
the interceding role of commercialization as an industry by itself in Malaysian context. The study conducted under fundamental concept of an industry criteria, contribution, value and perspective in Malaysia, focuses in research commercialization in university, which consist of IPTA (government benefactor universities) and IPTS (private benefactor universities). Besides, the study expands the research wing with small medium enterprises or SMEs linkage in the overall of university research commercialization intention. The study discusses on the Malaysian university commercialization, university-SME’s commercialization linkage and contribution towards becoming an industry by itself. The study also focuses on the role of commercialization, university and SME’s linkage, the contribution factor and industry perspective values of commercialization towards industrialization in Malaysia perspectives.